2021
DOI: 10.21203/rs.3.rs-736157/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative analysis of ChAdOx1 nCoV-19 and Ad26.COV2.S SARS-CoV-2 vector vaccines

Abstract: Vector-based SARS-CoV-2 vaccines have been associated with vaccine-induced thrombosis with thrombocytopenia syndrome (VITT/TTS), but the causative factors are still unresolved. We comprehensively analyzed ChAdOx1 nCov-19 (AstraZeneca) and Ad26.COV2.S (Johnson & Johnson). ChAdOx1 nCoV-19 contains significant amounts of host cell protein impurities, including functionally active proteasomes, and adenoviral proteins. In Ad26.COV2.S much less impurities were found. Platelet-factor 4 (PF4) formed complexes with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
0
10
0
4
Order By: Relevance
“…As far as we know, the differences between the vaccines are as follows: 1) The type of adenovirus is different (human Ad26 and chimpanzee adenovirus in the AD26 and ChA vaccines, respectively); 2) the human cell lines by which adenovirus are produced are different: T-REx-293 cells for ChA and PER.C6 TetR cells for AD26 [ 44 ]; 3) ChA contains a large number of host cell proteins differently from AD26 [ 10 , 44 , 45 ]; 4) chimpanzee adenovirus has a stronger negative charge than human AD26 [ 40 ]. Molecular simulations suggest that the chimpanzee adenovirus charge, combined with aspects of the virus shape, could allow it to bind to the positively charged PF4 protein [ 46 ]; 5) The number of viral particle in the AD26 vaccine is 3.3-fold higher than that in the ChA vaccine [ 47 , 48 ], possibly implying a higher spike protein and adenoviral protein burden.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, the differences between the vaccines are as follows: 1) The type of adenovirus is different (human Ad26 and chimpanzee adenovirus in the AD26 and ChA vaccines, respectively); 2) the human cell lines by which adenovirus are produced are different: T-REx-293 cells for ChA and PER.C6 TetR cells for AD26 [ 44 ]; 3) ChA contains a large number of host cell proteins differently from AD26 [ 10 , 44 , 45 ]; 4) chimpanzee adenovirus has a stronger negative charge than human AD26 [ 40 ]. Molecular simulations suggest that the chimpanzee adenovirus charge, combined with aspects of the virus shape, could allow it to bind to the positively charged PF4 protein [ 46 ]; 5) The number of viral particle in the AD26 vaccine is 3.3-fold higher than that in the ChA vaccine [ 47 , 48 ], possibly implying a higher spike protein and adenoviral protein burden.…”
Section: Discussionmentioning
confidence: 99%
“…In phase III clinical trial of the ChAdOx1-nCov-19 vector vaccine, a few cases of transverse myelitis were reported (O'Reilly, 2020; Voysey et al, 2021). Moreover, serious neurological disorders were reported following different mRNA-based vaccination including transverse myelitis, Guillain-Barré syndrome, cranial nerve neuropathies, myelitis, and facial nerve palsy (García-Grimshaw et al, 2021;Lau & Galea, 2022;Malhotra et al, 2021;Michalik et al, 2022;Wan et al, 2022). A study reviewing case reports and case series reported the occurrence of variable central and peripheral nervous system complications in patients receiving gene-based vaccines including transverse myelitis, Guillain-Barré syndrome, and cerebral venous sinus thrombosis (Sriwastava et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The emergency-based WHO policy authorized the entry of the "operation warp speed" mRNA-based vaccines that were approved by the emergency use authorization by the US Food and Drug Administration after only one year of development. Although the published phase 3 clinical trials reported fewer side effects and minor non-fatal complications (Baden et al, 2021;O'Reilly, 2020;Sultana et al, 2020)b, the accumulating evidence of serious neurological (Michalik et al, 2022(Michalik et al, , 2022; S. J. Thomas et al, 2021;Wan et al, 2022) and cardiac complications (Cari et al, 2021;Dionne et al, 2021;Jabagi et al, 2022) as well as death reports (Torjesen, 2021) shortly after receiving the first (García-Grimshaw et al, 2021) and the second doses of mRNA-based vaccines casts heavy shades of doubt on the safety profile as well as the preclinical studies of such types of vaccines (European Medicines Agency (EMA), 2021).…”
Section: Of 20mentioning
confidence: 99%
See 1 more Smart Citation
“…Research into the causes is ongoing. Preliminary ndings hint that residual host cell protein in the vaccine solution, and the physical vaccine structure may contribute (5,6). Secretion of soluble spike protein from incorrectly spliced spike transcripts was also recently proposed as an adverse factor in VITT development (7).…”
Section: Introductionmentioning
confidence: 99%